2020
DOI: 10.22434/ifamr2019.0178
|View full text |Cite
|
Sign up to set email alerts
|

Relationship quality and supplier performance in food supply chains

Abstract: The importance of procurement relationships in food supply chains is increasing in importance due to issues of food safety, food security, changing consumer preferences, ethical concerns and greater awareness of the environmental impact of food production. Despite the considerable research on buyer-seller relationships in the marketing and management literature, only a small proportion of this has focused on procurement relationships between producers and buyers in food supply chains. Hence, this paper specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 121 publications
(143 reference statements)
2
25
0
Order By: Relevance
“…This fact agrees, in a way, with the work of Lees et al. (2020), which stated that despite the considerable research on buyer–seller relationships in the marketing and management literature, only a small proportion of it has focused on procurement relationships between producers and buyers in food supply chains.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This fact agrees, in a way, with the work of Lees et al. (2020), which stated that despite the considerable research on buyer–seller relationships in the marketing and management literature, only a small proportion of it has focused on procurement relationships between producers and buyers in food supply chains.…”
Section: Discussionsupporting
confidence: 89%
“…In general, many articles related to consumer trust were found, even when a search focused on the relationship of trust within supply chains was conducted. This fact agrees, in a way, with the work of Lees et al (2020), which stated that despite the considerable research on buyer-seller relationships in the marketing and management literature, only a small proportion of it has focused on procurement relationships between producers and buyers in food supply chains.…”
Section: Discussionsupporting
confidence: 86%
“…Prior studies have identified that trust is a key predictor of performance (e.g. Lees et al, 2020;Pentina et al, 2013). It can increase consumer loyalty (Park et al, 2017), satisfaction (Kim and Peterson, 2017), word-of-mouth (Wang et al, 2016), or reduce perceived risk (Siegrist et al, 2008), thereby enhance performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the transformation of food systems 6 in the last decades, farmer-buyer relationships had an essential role, where farmers and buyers started to coordinate food chains, increasing effective communication, reducing risk, uncertainty and transactions costs for mutual benefits (Reardon et al, 2009;Dlamini-Mazibuko et al, 2019;Lees et al, 2020). This transformation allowed a consistent supply of products that met high safety and quality standards (Mergenthaler et al, 2009;Bellemare and Lim, 2018).…”
Section: Farmer-buyer Relationshipsmentioning
confidence: 99%
“…Farmer-buyer relationships have been recognized as essential for the transformation of food systems 20 (Dlamini-Mazibuko et al, 2019;Lees et al, 2020). The transformation of food systems has been characterised by economic growth, globalisation, specialisation and the coordination between business partners (e.g., farmers, retailers, processors, input suppliers) and has allowed for a consistent supply of products that meet high safety and quality standards (Mergenthaler et al, 2009;Bellemare and Lim, 2018).…”
Section: Introductionmentioning
confidence: 99%